Forecast of meteorological values based on the model of a multilayer perceptron - Del, Irina V. (Proceedings of SPIE)
The model of a multilayer perceptron has been developed and implemented to predict precipitation in a few hours based on the current state of meteorological parameters. The estimate of the model accuracy was 0.86, i.e. 86% of precipitation or no precipitation forecasts are predicted correctly.